Conformational properties of DNA strands containing guanine-adenine and thymine-adenine repeats - Vorlicková, M; Kejnovská, I; Kovanda, J; Kypr, J (Nucleic acids research, 1998)
CD spectroscopy and PAGE were used to cooperatively analyze melting conformers of DNA strands containing GA and TA dinucleotide repeats. The 20mer (GA)10 formed a homoduplex in neutral solutions containing physiological concentrations of salts and this homoduplex was not destabilized even in the terminal (GA)3 hexamers of (GA)3(TA)4(GA)3, although the central (TA)4 portion of this oligonucleotide preserved the conformation adopted by (TA)10. This observation demonstrates that homoduplexes of alternating GA and TA sequences can co-exist in a single DNA molecule. Another 20mer, (GATA)5, adopted as a whole either the AT duplex, like (TA)10, or the GA duplex, like (GA)10, and switched between them reversibly. The concentration of salt controlled the conformational switching. Hence, guanine and thymine share significant properties regarding complementarity to adenine, while the TA and GA sequences can stack in at least two mutually compatible ways within the DNA duplexes analyzed here. These properties extend our knowledge of non-canonical structures of DNA.
Keywords: DNA; sekvence nukleotidů; heteroduplexy nukleové kyseliny; konformace nukleové kyseliny; Base Sequence; Nucleic Acid Conformation; Electrophoresis, Polyacrylamide Gel; Dinucleotide Repeats; Nucleic Acid Heteroduplexes; elektroforéza v polyakrylamidovém gelu; dinukleotidové repetice; cirkulární dichroismus; Circular Dichroism